About review article "Biological agent in the treatment of Rheumatoid arthritis" (Journal of Bangladesh College of Physicians and Surgeons, 2011)
DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7959 (J Bangladesh Coll Phys Surg 2011; 29: 111)